State of World Population 2011 - United Nations Population Fund (United Nations, 2011)
In late 2011, the global population will reach 7 billion, up from 6 billion in barely 12 years. This Report examines how the world got to this milestone, mentioning factors such as the big strides in health care that allow older people to live longer, more children to survive to adulthood and beyond, as well as policies and other initiatives that allow women to play a stronger role in society. This overview includes analysis of the latest demographic trends, such as the unprecedented youth bulge, as well as projections and implications for the quality of life of women, men and young people. The Report includes original reporting from China, Egypt, Ethiopia, Finland, India, Mexico, Mozambique, Nigeria and the Former Yugoslav Republic of Macedonia.